COMMUNITY-BASED PARTICIPATORY RESEARCH TO INFORM SOCIAL SERVICE INTERVENTIONS - Norah Abdu Ahmed Zailay, Zamzam Ali Sahli, Maram hussin Mohammed Banajiah, ⁠Turki Mohammed Ahmad Abbas, ⁠Ibrahim Bati Al Mutairi, ⁠Kahla Hajilan Jumaan Al-Ghaidani, Jawaher Tami H Alkahtani, ⁠⁠ Bader Dahi R Alanezy,; Hadi Munawer A Alotaibi, Meaad Khaweld Nasser Alotibi, ⁠⁠Ali Qasem Al Darbashi, Taghreed Mohammed Al Musalem, ⁠Ali Hussain Ali Al-Hayder, Omar Mohammed Altariqi (Chelonian Research Foundation, 2022)
The aim of this review is to analyze and differentiate the principles, objectives, methods, and results of human-centered design (HCD) and community-based participatory research (CBPR) tackles in addressing public health concerns. Additionally, it aims to suggest ways in which HCD can be integrated into CBPR collaborations and initiatives. Through the examination of published literature, primary sources, and consultations with experts in both techniques, a team of researchers conducted a three-phased process to analyze and compare the primary differences and similarities between HCD and CBPR. They also developed suggestions for incorporating HCD tactics into CBPR initiatives. There are five Human-Centered Design (HCD) tactics that may be easily integrated into Community-Based Participatory Research (CBPR) projects to enhance results: (1) assemble transdisciplinary teams, (2) prioritize empathy, (3) engage and collaborate with "extreme users," (4) Efficiently develop prototypes and (5) produce real goods or services. Incorporating Human-Centered Design (HCD) into Community-Based Participatory Research (CBPR) projects may result in solutions that have a wider impact, are more easily accepted, are more efficient, and bring creativity to public health services, goods, and policies. Keywords: human-centered design (HCD), community-based participatory research (CBPR), review, differences, similarities, social service.